Chlorhexidine is Effective for Preventing Neonatal Infections and Death. (June 2015) - Carter, David
Abstract : According to this study: Chlorhexidine used for the care of skin and umbilical stumps is an effective and inexpensive way to reduce neonatal infections in developing countries. In the community setting, topical chlorhexidine use reduced neonatal mortality by 12%.